2014
DOI: 10.1371/journal.pone.0085866
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Relative Contribution and Hierarchy of hha and qseBC in the Regulation of Flagellar Motility of Escherichia coli O157:H7

Abstract: In recent studies, we demonstrated that a deletion of hha caused increased secretion of locus of enterocyte encoded adherence proteins and reduced motility of enterohemorrhagic Escherichia coli (EHEC) O157:H7. In addition to the importance of hha in positive regulation of motility, a two-component quorum sensing pathway encoded by the qseBC genes has been shown to activate bacterial motility in response to mammalian stress hormones epinephrine and norepinephrine as well as bacterially produced autoinducer-3. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Using a chemically synthesized fluorescent indole probe, we obtained evidence to support that indole could bind to the sensor protein Le-QseC in L. enzymogenes. The QseC/QseB signaling system is very important for the virulence and motility of enterohemorrhagic E. coli, which uses epinephrine/norepinephrine and AI-3 as signal molecules (35)(36)(37)(38)(39)(40). However, the nature of this so-called AI-3 remains unclear, other than that AI-3 was suggested to be a group of bacterial aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a chemically synthesized fluorescent indole probe, we obtained evidence to support that indole could bind to the sensor protein Le-QseC in L. enzymogenes. The QseC/QseB signaling system is very important for the virulence and motility of enterohemorrhagic E. coli, which uses epinephrine/norepinephrine and AI-3 as signal molecules (35)(36)(37)(38)(39)(40). However, the nature of this so-called AI-3 remains unclear, other than that AI-3 was suggested to be a group of bacterial aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…QseC is the membrane-bound sensor protein of the TCS with histidine kinase activity, and QseB is the cytoplasmic response regulator that regulates the expression of downstream target genes. QseC/QseB homologs are present in many important human and plant pathogens and are important for the virulence of pathogens (35)(36)(37). In enterohemorrhagic E. coli, QseC/QseB regulates multiple virulence factors and is known to respond to human epinephrine/norepinephrine and bacterial AI-3 (autoinducer 3), a group of mysterious signals whose identity is yet to be discovered (35)(36)(37)(38)(39)(40).…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested the modulatory role of Hha in enterobacteria through its interaction with DNA regulatory sequences ( Fahlen et al, 2001 ; Sharma and Zuerner, 2004 ; Sharma et al, 2005 ; Sharma and Bearson, 2013 ; Sharma and Casey, 2014 ). It is worth to remark that only in one of these reports ( Olekhnovich and Kadner, 2007 ) the Hha protein has been purified in an Δ hns genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two recent studies suggest that the transcription of the qseBC operon is also regulated by nucleoid‐associated proteins. Sharma & Casey () demonstrated that deletion of hha resulted in a decrease in motility of EHEC and compared the contribution and hierarchy of Hha and QseBC in controlling EHEC motility. Using single and double gene deletion mutants, they showed that transcription of qseC was significantly reduced in a hha ‐deficient background relative to wild‐type or a complemented strain and that hha was hierarchically superior to qseBC in regulating motility.…”
Section: Activation Of Qseb and Transcriptional Regulation Of Qsebcmentioning
confidence: 99%